ANALISIS KEMAMPUAN PEMODELAN MATEMATIS ANAK-ANAK DI KAMPUNG ADAT BOTI - Melkianus Tanu; Uke Ralmugiz; St. Muthmainnah Yusuf (MEGA: Jurnal Pendidikan Matematika, 2022)
Analysis of the Children’s Mathematical Modeling Ability in Boti Traditional Village, Kupang. Academic Year 2020/2021. Skripsi. Mathematics Education Study Program. Faculty of Teacher Training and Education. University of Muhammadiyah Kupang. This study aims to determine the mathematical modeling ability of children in the traditional village of Boti, which is very necessary in solving contextual problems completely because they do not understand the problem and do not able to convert the problem into a mathematical model. This research isqualitative research with a descriptive approach. The subjects of this study were 7 children in Boti traditional village. There were 3 interview test respondents who were selected based on the high, medium, and low ability categories. Data collection techniques used were data reduction, data presentation, and drawing conclusion. The validity of the data tested using a triangulation of data technique. Based on the results of 3 essay test items, it showed that the mathematical modeling ability has 3 categories, namely: 1 high-ability child, 4 moderately capable children, and 2 low-ability children.